Pengembangan Media Scrapbook Pada Pembelajaran Tematik Untuk Meningkatkan Minat Belajar Siswa Kelas I Sekolah Dasar - Cholifah, Tety Nur; Fauziah, Winda Novy (UNIB Press, 2021)
Teaching and learning activities need to support learning, namely learning media. Learning media is a tool to convey subject matter to students. The purpose of this study is (1) Knowing the feasibility of learning mediascrapbook in the thematic learning of first grade elementary school (2) Knowing the suitability of scrapbook media to increase interest in learning of first grade elementary school students. The type of research used is development research or research and development (R&D) with the Borg and Gall development model. The subjects of this study were the first grade students of Brongkal State Elementary School, which amounted to 22 students. The data collection technique used is a questionnaire. The data analysis technique for media feasibility uses quantitative descriptive and interest in learning uses the paired sample t test t test.